A social history of white working class women in industrializing Port Elizabeth, 1917-1936 - Gibbs, Patricia Anne (Rhodes University, Faculty of Humanities, Department of History, 1998)
The study period saw a significant increase in the urbanisation of whites and blacks in Port Elizabeth induced by droughts and coercive legislation, but also by burgeoning industrialisation. Industry had been given great stimulus by World War 1 and maintained by protectionist legislation in the 1920s which the local state and industrialists came to endorse. The ethos of the town was overwhelmingly British in terms of the population, the composition of the local council, business interests and the prevailing culture. Whites formed the largest component of the population in Port Elizabeth during the inter-war years. The majority of white women lived in the North End, the industrial hub and a major working class area of the city. Although the provision of housing was initially neglected, economic and subeconomic housing in the 1930s helped to create both racial separation and a sense of community between sectors of the working class. Yet, white working class women did not form a homogenous group, but rather consisted of different ethnic groups, occupations and classes. The Afrikaans speaking sector, formed a significant component of the industrial labour force especially in the leather, food and beverage and clothing industries. In a centre where white labour was favoured and marketed as an advantage to outside investors, they rapidly displaced coloured women. The female workforce was basically young, underpaid (especially in comparison to wages on the Rand) and temporary. While white women were still in evidence in other occupations such as domestic work and in the informal sector, their numbers here steadily diminished as both racial segregation and municipal regulation, were implemented. Against a background of chaotic social conditions, large slum areas and the spread of infectious diseases, the local council did much to improve health services particularly for women and children. Poor relief instituted in 1919 was, however, less forthcoming and female - headed households were often left to rely on the services of local welfare organisations. The extended family, however, was the norm affording support against atomization. Although pressurised by social ills throughout the period, the family was increasingly buttressed by state assistance. Prevailing morality was likewise actively constructed in terms of legislative repression and racial division. This often lead to social aberrations such as infanticide which was only reduced by the increase of state assistance and, in the longer term, social mobility of the whites.
Keywords: Women -- South Africa -- Port Elizabeth -- History; Women -- Employment -- South Africa -- Port Elizabeth -- History; Port Elizabeth (South Africa) -- History